O związkach podstawowych teorii powłok plastycznych - Duszek, M.; Sawczuk, A. (Engineering Transactions, 1970)
This paper presents a discussion of the relationships of the theory of plastic shells made of incompressible material. Given are the assumptions of the theory departing from the classic assumptions of Kirchhoff-Love, and by means od estimation of the order of magnitude of the particular terms in the expression for velocity and energy dissipation, the corresponding set of forces and velocities of deformations are obtained. The set of equilibrium equations and the boundary conditions are given, together with the principles of determining the equations of the yield surfaces.